2020
DOI: 10.3389/fncel.2020.555591
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Brd4 by JQ1 Promotes Functional Recovery From Spinal Cord Injury by Activating Autophagy

Abstract: Spinal cord injury (SCI) is a destructive neurological disorder that is characterized by impaired sensory and motor function. Inhibition of bromodomain protein 4 (Brd4) has been shown to promote the maintenance of cell homeostasis by activating autophagy. However, the role of Brd4 inhibition in SCI and the underlying mechanisms are poorly understood. Thus, the goal of the present study was to evaluate the effects of sustained Brd4 inhibition using the bromodomain and extraterminal domain (BET) inhibitor JQ1 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…40 mg/kg pentobarbital sodium 4% ( w / v ) was intraperitoneally administered in mice, and laminectomy was performed to remove the part of the vertebra covering the T9-T10 segment of the spinal cord. Then, a 10 g weight steel rod was adopted to damage the exposed spinal cord from 20 mm height, resulting in a moderate contusive SCI model [ 22 , 23 ]. After the surgical operation, the bladders of the mice were manually emptied twice a day until the bladder's function recovered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 mg/kg pentobarbital sodium 4% ( w / v ) was intraperitoneally administered in mice, and laminectomy was performed to remove the part of the vertebra covering the T9-T10 segment of the spinal cord. Then, a 10 g weight steel rod was adopted to damage the exposed spinal cord from 20 mm height, resulting in a moderate contusive SCI model [ 22 , 23 ]. After the surgical operation, the bladders of the mice were manually emptied twice a day until the bladder's function recovered.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity the spinal cord. Then, a 10 g weight steel rod was adopted to damage the exposed spinal cord from 20 mm height, resulting in a moderate contusive SCI model [22,23]. After the surgical operation, the bladders of the mice were manually emptied twice a day until the bladder's function recovered.…”
mentioning
confidence: 99%
“…Kornicka et al [49] reported that 5-azacytydine and resveratrol via modulation of autophagy reverse senescence and apoptosis of adipose stem cells. BRD4 reduces apoptosis induced by oxidative stress after spinal cord injury by regulating autophagy [50]. Mu et al [20] showed that BRD4 inhibits autophagy mediated by PINK1/Parkin to prevent high-fat diet-induced diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The BMS score of mice ranges from 0 (completely paralysis) to 9 (normal locomotion). For the inclined plane test, mice were placed on a rubber board, and then, the angles at which the mice could not hold its position for 5 sec were defined as the maximum angles, which could be used to evaluate the hind limb strength of mice [ 31 ]. The results of mouse hind limb movements were blindly recorded by two trained investigators.…”
Section: Methodsmentioning
confidence: 99%